OPTIMALISASI MEDIA SOSIAL INSTAGRAM UNTUK MENINGKATKAN JANGKAUAN AUDIENS UMKM: STUDI KASUS WEAR BY NILA - Agrina, Camelia Rizki; Prasetyo, Andreas Recki; Kirana , Desty Hapsari (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This community engagement activity aims to enhance the digital marketing capacity of MSMEs through social media management assistance, using Wear by Nila—an MSME operating in the Muslim fashion sector—as a case study. The approach employed is participatory and collaborative, involving students and business owners in the processes of planning, content production, publication, and evaluation on the Instagram platform. The strategies implemented include content planning, strengthening visual identity, and the selective use of Instagram Ads. The results show a significant improvement in posting consistency, audience reach, user engagement, and the partner’s understanding of the importance of digital marketing strategies. Furthermore, this activity demonstrates that direct support from academics can help MSMEs overcome resource limitations while driving sustainable digital transformation. This program implies that a practice-based mentoring model can be replicated as a strategic contribution of higher education institutions in supporting MSME empowerment in the digital economy era.